Applying the Cell-Based Coagulation Model in the Management of Critical Bleeding. Issue 2 (March 2017) - Ho, K. M.; Pavey, W.
The cell-based coagulation model was proposed 15 years ago, yet has not been applied commonly in the management of critical bleeding. Nevertheless, this alternative model may better explain the physiological basis of current coagulation management during critical bleeding. In this article we describe the limitations of the traditional coagulation protein cascade and standard coagulation tests, and explain the potential advantages of applying the cell-based model in current coagulation management strategies. The cell-based coagulation model builds on the traditional coagulation model and explains many recent clinical observations and research findings related to critical bleeding unexplained by the traditional model, including the encouraging results of using empirical 1:1:1 fresh frozen plasma:platelets:red blood cells transfusion strategy, and the use of viscoelastic and platelet function tests in patients with critical bleeding. From a practical perspective, applying the cell-based coagulation model also explains why new direct oral anticoagulants are effective systemic anticoagulants even without affecting activated partial thromboplastin time or the International Normalized Ratio in a dose-related fashion. The cell-based coagulation model represents the most cohesive scientific framework on which we can understand and manage coagulation during critical bleeding.